Modelling the water balance in the glacierized Parón Lake basin (White Cordillera, Peru) - Suarez, Wilson (2008)
The White Cordillera (northern Peru), with a glacial surface of 631 km2, is the largest glacierized mountain range in the Tropics. Due to the lack of physical data from most of its sub-basins, it is difficult to build a physical model to estimate the water resource flowing from the glaciers at the present time and a fortiori for the future. The most recent GCM simulations indicate a significant increase in the temperature and an accelerated shrinking of the glaciers. Consequently, we sought a model that would be based on the data available within instrumented sub-basins. A theoretical/conceptual water model makes it possible to quantify the local glacier contribution, which could then be applied to the other non-instrumented sub-basins. A total of 43.6% of Parón Lake's instrumented sub-basin area (47.4 km2) corresponds to glacial surfaces. Within this sub-basin, a smaller watershed (8.8 km2), called Artesón, with 72.9% glacierized area, has been accurately observed over a 5-year hydrological period (September 2000-August 2005). This information allowed us to calibrate the model over the Artesón sub-basin. The parameters obtained were applied to the entire Parón basin using the same modelling approach.